Uniqueness and Multiplicity of Solutions for a Second-Order Discrete Boundary Value Problem with a Parameter - Xi-Lan Liu; Jian-Hua Wu (Discrete Dynamics in Nature and Society)
This paper is concerned with the existence of unique and multiple solutions to the boundary value problem of a second-order difference equation with a parameter, which is a complement of the work by J. S. Yu and Z. M. Guo in 2006.